Goodnight Trump - Origen, Erich; Golan, Gan (Little, Brown and Company, 2018)
Parodying the soothing incantations of Goodnight Moon by Margaret Wise Brown with illustrations by Clement Hurd, GOODNIGHT TRUMP opens in the very classy golden bedroom of the White House, where it is bedtime for the 45th President of the United States. In this wickedly funny update to the bedtime classic, readers can encourage this very stable genius to bid a gentle goodnight to some of his favorite things, including his stuffed animal (what else but a Playboy bunny), his best friends from Russia, his Twitter feed, and his 12-pack of Diet Coke. GOODNIGHT TRUMP is a perfect gift for those who lean to the left -- offering readers the chance to put America's man-child-in-chief to bed early, so children everywhere can have sweet dreams without fear of being torn from their homes and families.